Protective Effect of Methylcellulose during Cryopreservation of Inoculated Cells in Serum-Free Medium - Koschiy, Svetlana V.; Goltsev, Anatoliy N.; Vysekantsev, Igor P.; Martsenyuk, Valentina F.; Gurina, Tatyana M.; Sokol, Larisa V. (Problems of Cryobiology and Cryomedicine, 2013)
There was experimentally shown a possibility to replace blood serum for methylcellulose (MC) in the media for cryopreservation of inoculated cells. Combination of 0.1% MC with 5% dimethyl sufoxide (DMSO) in the preservation media provided the highest indices of post-thaw cell survival. Freeze-thawing of cells in the medium contained MC, but without DMSO resulted in a significant reduction of survived cells. The cells, which were pre-cultured in the medium with 0.5% fetal serum (FS) and 0.1% MC, showed higher survival post freeze-thawing in serum-free medium comparing to the cells, which we pre-cultured in the medium with 10% FS. Probl Cryobiol Cryomed 2013; 23(2):116–123.